Microglial Lyzl4 Facilitates β‐Amyloid Clearance in Alzheimer's Disease - Jie Pan; Jie Zhong; Ji Geng; Jane Oberhauser; Shihua Shi; Jun Wan (Advanced Science)
Abstract Alzheimer's Disease (AD) is a neurodegenerative condition characterized by the accumulation and deposition of amyloid‐β (Aβ) aggregates in the brain. Despite a wealth of research on the toxicity of Aβ and its role in synaptic damage, the mechanisms facilitating Aβ clearance are not yet fully understood. However, microglia, the primary immune cells of the central nervous system, are known to maintain homeostasis through the phagocytic clearance of protein aggregates and cellular debris. In this study, RNA sequencing analysis and live cell functional screens are employed to uncover microglial genetic modifiers related to AD. Lyzl4 is identified, which encodes a c‐type lysozyme‐like enzyme primarily localized to microglial lysosomes, as a gene significantly upregulated in AD microglia with aging and propose that Lyzl4 upregulation acts as a positive regulator of Aβ clearance. Furthermore, it is found that Lyzl4 overexpression boosts Aβ clearance both in vitro and in vivo, underscoring its potential for mitigating Aβ burden. These novel insights position Lyzl4 as a promising therapeutic target for Alzheimer's disease, paving the way for further exploration into potential AD treatments.